Ursolic acid suppresses triple-negative breast cancer progression through mediating FABP4/PPARG pathway - Ying Deng; Junyi Wu; Di Pan; Wan Su; Songpo Wang (European Journal of Medical Research)
Abstract Background Triple-negative breast cancer (TNBC) remains the deadliest subtype of breast cancer owing to high metastatic potential and poor prognosis. Herein, we examined the antitumor effects of ursolic acid (UA), a pentacyclic triterpene compound, against TNBC and the underlying mechanisms. Methods TNBC cells were exposed to a graded concentration of UA, and cell proliferation and migration were examined through CCK-8 and wound healing assays. Transcriptome data of 116 TNBC and 290 normal tissues were acquired for determining differentially expressed genes. Using the PubChem and the SwissTargetPrediction, potential UA targets were inferred. 10 pairs of human TNBC and normal tissues were gathered for examining the expression of UA targets FABP4 and PPARG. The influence of FABP4/PPARG knockdown and overexpression on the therapeutic effects of UA was then observed. Results UA treatment hampered proliferation and migration of TNBC cells in a concentration-based fashion. FABP4 and PPARG were determined as targets of UA. Their expression levels were gradually elevated as the increase of UA concentration. Clinically, TNBC tumor tissues displayed notable down-regulation of FABP4 and PPARG in comparison with normal tissues. UA treatment increased PPARG expression and promoted its activation, which could be effectively attenuated by FABP4 knockdown. In addition, the efficacy of UA on suppressing TNBC cell growth and migration was notably reversed and enhanced by FABP4/PPARG knockdown and overexpression, respectively. Conclusions This study suggests that UA treatment increases PPARG expression through modulating FABP4, thus preventing TNBC progression, expanding the clinical application of UA and providing a theoretical basis for its usage in TNBC treatment.